Conception of developing the dynamically similar downscaled medium-range passenger airplane model for in-flight testing. (January 2021) - Olejnik, Aleksander; Kachel, Stanisław; Rogólski, Robert; Milczarczyk, Jarosław
The article describes the proposition for developing the similar dynamically downscaled model of a medium range passenger aircraft and its application for researches in area of aerodynamics and flight dynamics. Computer simulations of aerodynamic flows are commonly used in advanced aircraft designing. Numerous data on the characteristics of an airplane can be obtained from tunnel tests of geometrically scaled models. To get complete characteristics from both stable and unstable flight conditions, dynamically scaled models are constructed and applied in static or dynamic tests. The dynamically similar scaled model is, in fact, a reduced model of the real airplane which has specific qualities similar to qualities of a real aircraft and these relations are strictly defined with specific similarity numbers (factors). The article presents methodology for determining scale factors in relation to geometric, aerodynamic, and structural properties (mass, stiffness) of the aircraft. The methodology will be presented on the example of Tu-154 aircraft that crashed in April 2010 with the President of the Republic of Poland and many military and government officials on board. Dynamically similar downscaled model was designed in Faculty of Mechatronics and Aerospace of the Military University of Technology (FMA MUT, Warsaw, Poland) and is still being developed in the framework of ongoing research project. This paper presents only general assumptions taken for the process and the current stage of successively developed model.